Paradiplomasi Bandung Menuju Kota Wisata Halal - Windy Dermawan; Akim Akim; Henike Primawanti (Indonesian Perspective, 2020)
This research aims to analyze paradiplomacy of Bandung City towards global public in the development of halal tourism. Paradiplomacy becomes important for subnational actors in the development of local resources and the use of foreign resources. Potential areas that have the opportunity to be developed is halal tourism, which is one of the new trends in tourism in the world. The Bandung city is one of the leading regions in the creative economy in West Java that sees this potential and participates in driving regional development through halal tourism. The method in this research is qualitative by collecting data through interviews and documentation studies. This research found that paradiplomacy became one of the instrument of the Bandung city in the utilization of foreign sources through halal tourism. Bandung City Government interacts toward global public by introducing Bandung as one of the destination in halal tourism. The results of this research also show that the paradiplomacy of the Bandung city is carried out through several stages, including introducing halal tourism to the global public, increasing positive appreciation of halal tourism, strengthening relationships with other actors abroad and influencing it by bringing cooperation with other actors.